Dupilumab for the treatment of asthma. (4th March 2017) - Santini, Giuseppe; Mores, Nadia; Malerba, Mario; Mondino, Chiara; Anzivino, Roberta; Macis, Giuseppe; Montuschi, Paolo
ABSTRACT: Introduction : Dupilumab (REGN668/SAR231893), produced by a collaboration between Regeneron and Sanofi, is a monoclonal antibody currently in phase III for moderate-to-severe asthma. Dupilumab is directed against the α-subunit of the interleukin (IL)-4 receptor and blocks the IL-4 and IL-13 signal transduction. Areas covered : Pathophysiological role of IL-4 and IL-13 in asthma; mechanism of action of dupilumab; pharmacology of IL-4 receptor; phase I and phase II studies with dupilumab; regulatory affairs. Expert opinion : Patients with severe asthma who are not sufficiently controlled with standard-of-care represent the target asthma population for dupilumab. If confirmed, efficacy of dupilumab in both eosinophilic and non-eosinophilic severe asthma phenotype might represent an advantage over approved biologics for asthma, including omalizumab, mepolizumab, and reslizumab. Head-to-head studies to compare dupilumab versus other biologics with different mechanism of action are required. Pediatric studies with dupilumab are currently lacking and should be undertaken to assess efficacy and safety of this drug in children with severe asthma. The lack of preclinical data and published results of the completed four phase I studies precludes a complete assessment of the pharmacological profile of dupilumab. Dupilumab seems to be generally well tolerated, but large studies are required to establish its long-term safety and tolerability.